HYDRAULIC CONTROL SYSTEMS IN TECHNICAL AND INFORMATION TECHNOLOGY EDUCATION - SLEZIAK, Mariusz (Trends in education, 2012)
Mechatronics is used in both large companies and small manufacturing plants. One of the areas of mechatronics is a hydraulic. The classes with students towards TechnicalInformation Education activities were introduced to the hydraulic control systems. From this perspective, it is important to conduct classes in well-equipped laboratories mechatronics.
Keywords: hydraulics; mechatronics; technical - information education; training.